Empowerment of Zakat Maal in Improving the Welfare of Mustahik from the Perspective of Islamic Economics at Baznas Sintang Regency - Fatmawati, Ela; Sumar’in, Sumar’in; Arnadi, Arnadi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Zakat is a mandatory wealth that must be issued by every Muslim who is considered capable, with certain conditions that must be met. In Indonesia, zakat is distributed by the National Amil Zakat Agency (BAZNAS). Unfortunately, in the management of zakat at BAZNAS Sintang Regency, there are still many pending proposal requests, resulting in many mustahik (zakat recipients) not receiving zakat. The research focuses on: 1) How is the planning of zakat management at BAZNAS Sintang Regency? 2) What is the strategy for collecting zakat at BAZNAS Sintang Regency? 3) How is the distribution of zakat at BAZNAS Sintang Regency? and 4) What are the supporting and inhibiting factors for zakat at BAZNAS Sintang? The method used is field research, which is a qualitative descriptive study. The research was conducted through direct interviews with the Head of BAZNAS and several mustahik. The results show that the zakat funds distributed must be in accordance with the 8 asnaf (categories of zakat recipients). The distribution of zakat maal managed by BAZNAS Sintang Regency is based on the amount of zakat funds received, and is adjusted according to Islamic principles using two methods: consumptive and productive methods. However, the distribution of zakat has not been optimal because it does not fully meet the principles of Islamic Economic Law, such as justice, tauhid, al-maslahah, and others.